Sodium alginate capsulation increased brain delivery of probucol and suppressed neuroinflammation and neurodegeneration - Mamo, J.; Lam, Virginie; Al-Salami, Hani; Brook, E.; Mooranian, A.; Nesbit, M.; Graneri, L.; D'Alonzo, Z.; Fimognari, N.; Stephenson, A.; Takechi, Ryu (2018)
© 2018 2018 Newlands Press. Aim: To enhance the bioavailability and brain uptake of probucol and examine whether it attenuates neuroinflammation and neurodegeneration by utilizing a sodium alginate nanoencapsulation technique. Materials & methods: Wild-type mice were given either low-fat standard chow, high-fat (HF) diet to induce neuroinflammation and neurodegeneration, HF diet supplemented with nanocapsuled probucol at a concentration of 0.1% (w/w), HF diet supplemented with noncapsulated probucol at the same concentration of 0.1%, or HF diet supplemented with noncapsulated probucol at higher concentration (1%) for 24 weeks. Results & conclusion: The nanoencapsulation increased the plasma and brain concentration of probucol significantly compared with the mice that was given the same dosage of probucol without capsulation, and significantly suppressed the neuroinflammation and neurodegeneration.